1989
DOI: 10.1258/002367789780886984
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented spleens in C57BL mice

Abstract: Approximately 15% of our highly inbred C57BL/6 mice show a spleen with a pigmented cranial part. Microscopically, abundant aggregates of pigment granules are observed primarily scattered between cells of the red pulp. They give a positive reaction with Perls' Prussian blue and stain heavily with silver-methenamine. Most of the granules are stored in macrophages. In some cases a number of granules are surrounded by a membrane. This abnormality may be designated haemosiderosis. In the present study we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…We found this accumulation to fluctuate greatly between mice, suggesting that it may depend on the 129͞Sv ϫ C57BL͞6 hybrid strain background of each animal. This natural iron storage has been previously reported in C57BL͞6 mice and was described to occur mainly in splenic macrophages (16,17). Surprisingly, in spleen of Usf2 Ϫ/Ϫ mice, iron levels remained very low (Fig.…”
Section: Resultssupporting
confidence: 81%
“…We found this accumulation to fluctuate greatly between mice, suggesting that it may depend on the 129͞Sv ϫ C57BL͞6 hybrid strain background of each animal. This natural iron storage has been previously reported in C57BL͞6 mice and was described to occur mainly in splenic macrophages (16,17). Surprisingly, in spleen of Usf2 Ϫ/Ϫ mice, iron levels remained very low (Fig.…”
Section: Resultssupporting
confidence: 81%
“…For all new radiotracers tested, radioactive signal was observed in the eyes, which supported the specific uptake in melanin-rich tissues; however, the study was conducted in C57BL/6J mice that have high melanin pigmentation in the eyes , (as well as skin, hair, and spleen). Because of the large differences between murine and human ocular geometry as well as uveal melanin content, radioactivity uptake in the eyes may not be an issue for clinical transfer . Additionally, the first in human study of a similar benzamide-type radiotracer developed by our research group ([ 18 F]­MEL050) , indicated that the radiotracer is safe with suitable biodistribution for PET imaging…”
Section: Resultsmentioning
confidence: 77%
“…Some authors question the actual nature of the splenic pigment. Hemosiderosis (Veninga et al, 1989) is a less probable reason of splenic pigmentation (Weissman, 1967;Sundberg, 1991;Van der Heijden et al, 1995). There is also controversy be-Lack of spleen melanosis in old C57BL/6 mice tween melanin and lipofuscin -pigments of different characters and origin (Kent, 1976;Double et al, 2008).…”
Section: Melanin Degradation In C57bl/6 Animalsmentioning
confidence: 99%
“…The occurence of splenic melanosis varies between particular reports (10-21%, Weissman, 1967;8-34%, Crichton et al, 1978;15%, Veninga et al, 1989;23%, van der Heijden et al, 1995;14-80%, Plonka et al, 2005b) but rarely exceeds 30% (34% for female C57BL/6J and 31% for female C57BL/IOScSn, Crichton et al, 1978; 50-80% for female C57BL/6 in late catagen/early telogen, Plonka et al, 2005b). As the reason of this pigmentatory effect some authors suggested haemosiderins (Veninga et al, 1989) or lipofuscin (Crichton et al, 1978), but most of them, starting with Weissman (1967) and followed by Sundberg (1991), van der Heijden et al (1995, and recently by us (Plonka et al, 2005b), insist that melanin is the pigment responsible for the phenomenon.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation